Penyuluhan dan Pendampingan Pembuatan Peraturan Desa tentang Penerbitan Hewan Ternak di Desa Adolang Dhua Kecamatan Pamboang, Kabupaten Majene - Ardiansyah Ardiansyah; Aminuddin Aminuddin; Ahmad Abbas; Muhammad Aswad; Abdul Gaffar Haris; Nur Iman Saal (Abdimas Universal, 2024)
This Community Service activity is a continuation of the socialization activities of LKBH Abdi Keadilan in Adolang Dhua Village. During the activity, questions arose from various communities and confessions from the Village Head who asked how law enforcement against livestock that entered the yard and damaged residents' agricultural land. Because there are no clear rules at the village level regarding efforts to reduce the wildness of livestock that enter the community's cultivation and agriculture, the village head cannot provide solutions to the problem of livestock entering residents' land. Therefore, disputes between land-owning farmers and livestock owners are frequent. The Community Service methodology used is action research, one type of action research that is often known is Participation Action Research (PAR). That based on the results of community service activities on mentoring and drafting Adolang Dhua village regulations on Livestock Control using the Participation Action Research (PAR) method has run smoothly. The service team together with elements of the Adolang Dhua Village government, namely members of the Village Consultative Body and the Head of Adolang Dhua Village have succeeded in drafting Village Regulations that are in accordance with the proposals and expectations of the village community Adolang Dhua.